Malugo: A peer-to-peer storage system. (7th May 2010) - Chan, Yu-Wei; Ho, Tsung-Hsuan; Shih, Po-Chi; Chung, Yeh-Ching
We consider the problem of routing locality in peer-to-peer storage systems where peers store and exchange data among themselves. With the global information, peers will take the data locality into consideration when they implement their replication mechanisms to keep a number of file replicas all over the systems. In this paper, we mainly propose a peer-to-peer storage system – Malugo. Algorithms for the implementation of the peers' locating and file operation processes are also presented. Simulation results show that the proposed system successfully constructs an efficient and stable peer-to-peer storage environment with considerations of data and routing locality among peers.